Understanding community safety and policing in San José, California: A qualitative and communal analysis - Dao, Michael; De Bourbon, Soma; McClure Fuller, Melissa; Armaline, William; Worthen, Miranda (Frontiers in Sustainable Cities, 2022)
In Summer 2020, persistent public protest about racial injustice and police violence spurred conversations and action across the United States and the world about what community safety means and the various ways it can be achieved–particularly for diverse community members whose lives may be threatened under the status quo. In San José, California, this led in part to a community engaged research study on reimagining community safety–The People's Budget of San José. The project intended to inform justice policy reform in the city according to the perspectives and needs of residents. Through this community-academic partnership, 14 focus group discussions were held by community-based organizations where diverse groups of residents shared what community safety looked like to them, discussed what made them feel unsafe, learned about the city's budget, and identified how that budget reflects or is in opposition to their ideas about how to achieve safety. Utilizing a theoretical matrix that merges Capabilites Approach and Critical Race Theory and data were analyzed focusing on elements of community safety. Three themes came through the data: (1) basic human rights for vulnerable populations; (2) police, safety and sociocultural conditions; (3) space, race, and class within community safety. Findings from the study highlight the ongoing need to examine how communities perceive their own wellbeing and community safety exclusive of governmental authorities. We conclude with policy, practice, and research recommendations for how to deepen understandings of what “public safety” means in the eyes of residents and how it might be achieved in light of current politics.